O sexismo no ensino superior do Maranhão - NASCIMENTO, Felipe Bueno do (2017)
This study is part of gender relations, because talking about gender is talking about the relations between men and women, about the social roles reserved for them, taught and collected throughout life, in order to investigate sexism in higher education. The gender category is the social construction of what is feminine or masculine, since sexism is discrimination based on the sex of each person. Women are presented as the main victims of sexism, but the intention here was to measure the effects of this phenomenon among women and men who attend the same university banks. In this way, the research universe of this study composes a sample of 476 subjects (220 men and 256 women) students from 28 UFMA undergraduate courses. The research instrument applied to the students was drawn from the adaptation of instruments previously proposed by other researchers. Thus, the research instrument of this study is a questionnaire composed of three stages, each of them being responsible for a dimension of analysis: Profile of the subject; Sexist perceptions; and Academic Reality. After data collection, they were tabulated in the Statistical Package for the Social Sciences - SPSS. In general, it is assumed that students do not appear to have sexist perceptions, but analysis through specificities has shown more interesting elements. The main results were: Most students mark the woman's place through stereotypes like wearing skirts, makeup, nails, playing house, or using objects in pink. Men and women can be sexist in the same way. Social class is no justification for a higher level of sexism, but the level of education is. Religious people show a greater tendency towards sexist perceptions, with the Catholic religion being the predominant among them. Both left and right have shown themselves to be sexist. Only the minority of the sample subjects proclaimed themselves feminist, and the observable is that the higher the level of sexism, the greater the rejection of feminism. The existence of courses considered "for men" and courses considered "for women" has been proven, but most of the subjects in this study do not agree with this differentiation. The men had their professional capacity contested in few courses, in low proportion, but when it happened, it was in courses considered feminine. Already women had their professional capacity challenged in almost all courses, in high proportion and regardless of whether the course is considered female or male. Both sexes indicate that they have already been targets of suspicion about the potential of their abilities simply because they are men or women, but women have suffered much more from this problem. More than 82% of the subjects in this study have already witnessed prejudicial trotters in the institution, most of them involving macho and sexist attitudes. Within the classroom, 56% of the students already witnessed teachers making biased jokes, and also, in this case, most of them were sexist or sexist content. Another worrying fact was the high rate of responses pointing to the occurrence of racist jokes. Complaining to these practices occurs in only 9% of cases, because most of the time the reaction of the class is to smile. The overall average of men and women who suffered sexual harassment at university was 14% and 24%, respectively. The stalkers in general are the colleagues, but for 28% of the women were the teachers themselves. When they return home, men's greatest fear is that they are robbed, while women are being raped. One in three women in this study has been harassed on the bus that makes the universitycenter stretch of the city. Men also report sexual abuse on the bus, but far fewer than women. It was then observed the presence of sexism, both in the level of perception of the students themselves and in everyday elements in the university environment.